2012
DOI: 10.1016/j.aquatox.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

UV-B affects photosynthesis, ROS production and motility of the freshwater flagellate, Euglena agilis Carter

Abstract: The effects of ultraviolet B (UV-B; 295-320 nm) radiation on certain vital physiological (photosynthesis), biochemical (production of reactive oxygen species - ROS) and behavioral (motility and orientation) characteristics were investigated in the unicellular photoautotroph, Euglena agilis Carter. The photosynthetic performance of E. agilis was recorded after exposure of between 15 and 60 min followed by a period of recovery lasting 6-24h under dim light (5-10 μmol photons m(-2) s(-1)). The maximum quantum yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…In this study, several antioxidant response elements, such as HSF and AP-1, were predicted in the 5′-flanking region of AccGSTO2. Furthermore, the qPCR analysis revealed that AccGSTO2 was induced by all abiotic stressors examined, such as temperature, H 2 O 2 , insecticides and UV radiation can induce oxidative stress (Lushchak 2011;Kottuparambil et al 2012). Consistent with these results, GSTO from Bombyx mori is activated by a variety of environmental stimuli, including bacteria, ultraviolet-B (UV-B) and three commonly used chemical insecticides (Yamamoto et al 2011).…”
Section: Discussionsupporting
confidence: 66%
“…In this study, several antioxidant response elements, such as HSF and AP-1, were predicted in the 5′-flanking region of AccGSTO2. Furthermore, the qPCR analysis revealed that AccGSTO2 was induced by all abiotic stressors examined, such as temperature, H 2 O 2 , insecticides and UV radiation can induce oxidative stress (Lushchak 2011;Kottuparambil et al 2012). Consistent with these results, GSTO from Bombyx mori is activated by a variety of environmental stimuli, including bacteria, ultraviolet-B (UV-B) and three commonly used chemical insecticides (Yamamoto et al 2011).…”
Section: Discussionsupporting
confidence: 66%
“…Carotenoids, phenols and flavonoids are part of the secondary metabolism of red algae and serve as antioxidants (Zeng et al 2001;Apel & Hirt 2004;Ganesan et al 2008;Kottuparambil et al 2012). All three metabolites were in higher concentrations in the samples treated with 50 psu, but lower concentrations in those treated with 30 psu, the latter repeating the pattern and motif found with phycobiliproteins.…”
Section: Discussionmentioning
confidence: 60%
“…In D. melanogaster, the sole sigma class GST plays a dominant protective role against oxidative damage (Singh et al 2001; Alias and Induction of AccGSTS1 after exposure to various environmental stresses GSTs are known to be an important component of the oxidative stress response. Previous studies have indicated that environmental conditions such as temperature, heavy metals, salinity, pesticides, and UV radiation can induce oxidative stress (Lushchak 2011;Kottuparambila et al 2012). To elucidate the potential involvement of AccGSTS1 in antioxidant defense, transcripts of AccGSTS1 under cold (4°C), heat (43°C), H 2 O 2 , HgCl 2 , and insecticide (phoxim, cyhalothrin, and acaricide) exposure were examined by qPCR (Fig.…”
Section: Tissue and Stage-specific Expression Profiles Of Accgsts1mentioning
confidence: 99%